Intelligent leadership and its role in achieving organizational ambidexterity - Sabir Hamad, Daham; Zrar Abdulrahman, Abdulrahman; Saadallah rashed, Jwan (Iraqi Journal for Administrative Sciences, 2026)
This research aims to identify the role of intelligent leadership, with its dimensions (emotional intelligence, rational intelligence, spiritual intelligence, and interpersonal intelligence), in achieving the dimensions of organizational agility: exploratory agility, exploitative agility, and contextual agility. The research framework represents the research problem, which defined by posing several questions about the nature of the relationship and influence between the two variables. To this end, a theoretical framework designed, from which two main hypotheses were derived and subjected to multiple statistical tests. A questionnaire used as the data collection tool. The research adopted a descriptive-analytical approach, describing the main and sub-variables. The research population consisted of all managers at Korek Telecom in the Kurdistan Region of Iraq, totaling 150 managers. Accordingly, a comprehensive survey method used to determine the sample, distributing questionnaires to them. Only 127 questionnaires returned, achieving a response rate of 84.7%. The research hypotheses tested using SPSS version 26. The research yielded several conclusions, including the existence of positive correlations and significant impact relationships between the two variables at both the macro and micro levels. The research recommended leveraging the strong relationship between the two variables and directing it towards serving Korek Telecom, the company under study.